Personalized medicine for effective treatment of non-small-cell lung cancer with targeted therapies - Quan, Duong Hong (Academia Journal of Biology, 2020)
Lung cancer is the most common cause of cancer death worldwide, with most deaths having distant metastases. It has become increasingly complex to get effective treatment for lung cancer patients. While generalized medicine with traditional therapy resulted in comparatively poor response, personalized medicine has been well known to be an important strategy for effective treatment of lung cancer, with current focus on significant detection of clinical oncogenic drivers responsible for tumor initiation and maintenance and development of drug resistance. In lung cancer, especially in non-small-cell lung cancer (NSCLC), EGFR, ALK, RET, ROS1, BRAF, KRAS, NRAS, PIK3CA, DDR2, MET, ERBB2 have been reported to be key oncogenic drivers, which are targeted in the development and application of targeted therapeutic drugs. Personalized medicine based on these oncogenic drivers is highly recommended for treatment of advanced NSCLC patients. In this article, the significant application of personalized medicine based on the key oncogenic drivers for effective treatment of NSCLC with targeted therapeutic drugs is reviewed.